FE and skills – is the 'UK laboratory' open for expansive policy learning?. Issue 3 (3rd April 2019) - Hodgson, Ann; Spours, Ken; Gallacher, Jim; Irwin, Tracy; James, David
ABSTRACT: This article builds on the previous articles in this special issue to explore two related concepts – a 'UK policy laboratory' and 'expansive policy learning', with a specific focus on further education (FE) and skills. We argue that the potential for a UK policy laboratory in this area is based primarily on a new balance between the forces of convergence and divergence across the four countries of the UK. In this 'goldilocks zone' lie opportunities for policy learning. The methodology of the UK FE and Skills Inquiry, on which this article draws, attempted to model the conditions of the UK policy laboratory by involving a rich mix of social partners and highlighting the importance of national contexts and how these can inform differing approaches to common challenges. The Inquiry also identified 'interesting practice' that may form the basis of an initial 'common project' across the different systems. However, its pursuit will require shifts towards the more collaborative approach to FE and skills that characterises the three smaller countries of the UK. In this variegated political environment, we conclude by speculating on the wider conditions for the permanent development of a UK policy laboratory (or laboratories) and expansive forms of policy learning.